Adenosine-Guided Elimination of Dormant PV Conduction in Paroxysmal AF - Hitt, Emma (MD Conference Express, 2014)
Adenosine-guided elimination of dormant pulmonary vein (PV) conduction decreases recurrence of atrial tachyarrhythmias (ATs) in patients undergoing catheter ablation for paroxysmal atrial fibrillation (AF). This article presents data from the Adenosine Following Pulmonary Vein Isolation to Target Dormant Conduction Elimination trial [ADVICE; NCT01058980].